Comparing Educational Studies Curricula - Quang Huy, Mai (VNU Journal of Science: Education Research; Vol 34 No 1, 2018)
"Improving the quality of research staff and education specialists" is one of the tasks and solutions for education and training development. It is important to train qualified researchers and educators to meet international standards. Based on comparing the curriculum of the bachelor degree in educational studiesin our country with the the curriculum in Hiroshima University - Japan, the article clarifies the basis for building curiculum ofBA in educational studies in our country.